Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Media Pembelajaran Power Point pada Mata Pelajaran Bahasa Indonesia di Kelas IV MIN 2 Langkat - Enda lovita Pandiangan; Fahrunnisa Fahrunnisa; Rizka Hasibuan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
Resource Based Learning learning method is a learning process that directly confronts students with one or a number of learning resources individually or in groups with all activities related to learning resources. The author used this learning method to improve mastery of purification material for class VII MTsN 1 Langkat students. The subjects of this research were 35 class VII students at MTsN 1 Langkat. This research was carried out in two cycles, where each cycle consisted of planning, acting, observing and reflecting. The results of the research explain that learning outcomes for describing material have increased, in the first cycle of the first meeting, students' learning outcomes for describing material obtained an average score of 62.71 and at the second meeting, students' learning outcomes for analyzing material obtained an average of 67. In the cycle II the average learning outcomes increased, the first meeting of students' learning outcomes for analyzing material obtained an average score of 71.34 and the second meeting of students' learning outcomes for analyzing material obtained an average of 75.00. From the pretest before the action, the average value was 74.48 and the posttest results after the action obtained an average value of 87.17. If measured by N-gain, the average student ability is 0.49 in the medium category. This shows that Resource Based Learning according to MTsN 1 Langkat students is considered good, namely between 56-75% classification. Thus, the application of Resource Based Learning can improve students' ability to describe material